PENGARUH MODEL PEMBELAJARAN TALKING STICK MENGGUNAKAN MEDIA TONGKAT TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMA - Nursakirah Nursakirah; Mikrayanti Mikrayanti; Sowanto Sowanto (SUPERMAT : Jurnal Pendidikan Matematika, 2020)
This research was motivated by the low mathematics learning outcomes of class X students of a public high school in Bima City. To overcome this, a study was conducted using the talking stick learning model using stick media. The purpose of this study was to determine student learning outcomes in the material of three-variable linear equation system (SPLTV) class X one of the public high schools in Bima City for the 2020/2021 academic year through the influence of the Talking Stick learning model using stick media. This research is a quasi-experimental research design using a posttest-only control design. The population of this study was all class X students of one of the public high schools in Bima City for the 2020/2021 academic year, with the sample in this study only taking two groups, namely the experimental class and the control class. The instrument used in this study was a test of student mathematics learning outcomes. The data analysis was performed quantitatively using the t-test. The results showed that the use of the talking stick learning model using stick media had an effect on student learning outcomes in the material of the three-variable linear equation system for class X one of the public high schools in Bima City for the academic year 2020/2021.